The introduction of the five senses in the novel The Boy by Alia Mamdouh Prepare - Nima, Zainab Abdul-Mahdi (Al-Adab Journal, 2021)
the image of those senses that are employed as a reference for what I have chosen, other than me - the actual employment of those senses.I hope that we employ these senses in poetry or prose, as this requires a departure from their real function to a metaphorical one that is commensurate with the nature of these literary texts. It is known that the language of literature is a special language that transcends the language of writing and research, and this is what makes us meditate and stop at each word in the literary text, and we read it more than one reading to reach approaches that correspond to what the text wanted. The writer Alia Mamdouh in her novel (The Boy)